2007
DOI: 10.1038/sj.ki.5002087
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal pro brain natriuretic peptide predicts mortality in patients with end-stage renal disease in hemodialysis

Abstract: Concentrations of N-terminal pro brain natriuretic peptide (NT-proBNP) increase in patients with heart failure and other cardiovascular (CV) diseases and are strong prognostic markers. In patients with end-stage renal disease (ESRD) in hemodialysis (HD), levels of NT-proBNP are almost always raised. In ESRD patients undergoing HD, we aimed at (i) identifying the factors that affect levels of NT-proBNP, (ii) determining the effect of HD on NT-proBNP, and (iii) determining the prognostic impact of NT-proBNP. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
189
3
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(217 citation statements)
references
References 39 publications
19
189
3
6
Order By: Relevance
“…Thus, our study did not show any sustained association between log NT-proBNP and cardiac function as assessed by transthoracic echocardiogram or ATP myocardial perfusion scintography. Other studies have reported an association between BNP and markers of left ventricular hypertrophy rather than volume status (19,20); however, in one of these studies, BNP values were lower in those hemodialysis patients with greater residual renal function and thereby potentially less fluid-overloaded (20). In both of these studies, the median BNP values were substantially greater than those in our study (19,20), as were the levels of overhydration (20).…”
Section: Discussioncontrasting
confidence: 80%
“…Thus, our study did not show any sustained association between log NT-proBNP and cardiac function as assessed by transthoracic echocardiogram or ATP myocardial perfusion scintography. Other studies have reported an association between BNP and markers of left ventricular hypertrophy rather than volume status (19,20); however, in one of these studies, BNP values were lower in those hemodialysis patients with greater residual renal function and thereby potentially less fluid-overloaded (20). In both of these studies, the median BNP values were substantially greater than those in our study (19,20), as were the levels of overhydration (20).…”
Section: Discussioncontrasting
confidence: 80%
“…Our results remained robust, even after adjustment for eGFR and proteinuria and in subgroups stratified by eGFR, proteinuria, and diabetic status. NT-proBNP regulates BP and body fluid volume by its natriuretic and diuretic actions, arterial dilation, and inhibition of the renin-aldosterone-angiotensin system, 24 and increased levels of this marker likely reflect myocardial stress induced by subclinical changes in volume or pressure, even in persons without clinical heart disease. Our findings are consistent with prior studies of the general population that have shown NT-proBNP to be strongly associated with HF.…”
Section: Discussionmentioning
confidence: 99%
“…Because B-type natriuretic peptide (BNP) is released by the left ventricle in response LV end-diastolic wall stress (2), this biomarker has been studied as a predictor of patient outcome. Our group and others have demonstrated that a single elevated BNP concentration strongly predicts cardiovascular and all-cause mortality in patients undergoing dialysis (3,4). Concentrations of BNP are frequently elevated in patients with CKD, particularly those receiving dialysis, and more so for the inactive N-terminal end NT-BNP-76 than the active 32-amino acid peptide BNP-32 (3).…”
Section: Introductionmentioning
confidence: 89%